PENGARUH KEPEMIMPINAN, LINGKUNGAN KERJA, ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) DAN KOMITMEN ORGANISASI TERHADAP KINERJA PEGAWAI DI KANTOR KECAMATAN GONDANGREJO KABUPATEN KARANGANYAR - - Maryanto (JI@P, 2016)
This research aimed to analyse the citizenship behavior, and oforganizational commitment upon work performance of sub districtemployees at Gondangrejo Sub-District, Karanganyar Regency.Quantitative research strategy was used to analyse the mentionedresearch objective. All the employees of the Gondangrejo Sub-Districttotally 27 employees were selected as the respondents The linear multipleregression was employed to test the research hypothesis. Researchresult showed that there are effect of leadership style, work environment,organizational citizenship behavior, and organizatinal commitment,partially upon work performance. Research result also indicated that therewere impact of those four indenpendent variables simultaneously upunthe work performance.Key words: leadership style; work environment; organizational citizenship behavior;organizatinal commitment; work performance.